Origin and tentative identification of tri to pentaunsaturated ketones in sediments from Lake Fryxell, East Antarctica - Jaraula, Caroline; Brassell, S.; Morgan-Kiss, R.; Doran, P.; Kenig, F. (Elsevier Science, 2010)
Chromatographic and mass spectrometric analysis of surface sediments from perennially ice-covered Lake Fryxell (McMurdo Dry Valleys, East Antarctica) enabled tentative identification from mass spectral data of previously unreported pentaunsaturated ketones, octatriacontapentaen-2-one (C-38 Me-5), nonatriacontapentaen-3-one (C-39 Et-5) and tetradecapentaen-2-one (C-40 Me-5) In addition, the C-37, C-38 and C-40 alkenones occur as di, tri and tetraunsaturated compounds, whereas the C-39 alkenones only include the tetraunsaturated components Analysis of environmental DNA extracted from the water column of Lake Fryxell produced two 18S rDNA sequences closely related to Isochrysis spp, Chrysotila lamellosa and haptophyte sequences previously recognized in sediment samples collected from a Greenland lake and from Ace Lake, Antarctica. Based on the alkenone distribution, coupled with phylogenetic data, we propose that haptophytes related to Isochrysis and/or C lamellosa are the source organisms of alkenones in Lake Fryxell. The occurrence of pentaunsatured alkenones may represent a response to the year-round cold water temperature (ca. 1 degrees C average), likely combined with oxygen supersaturation and growth under light- and nutrient-limited conditions in the upper water column